Unraveling the Excited-State Dynamics and Light-Harvesting Functions of Xanthophylls in Light-Harvesting Complex II Using Femtosecond Stimulated Raman Spectroscopy - Artes Vivancos, Juan M. (J Am Chem Soc, 2020)
[Image: see text] Photosynthesis in plants starts with the capture of photons by light-harvesting complexes (LHCs). Structural biology and spectroscopy approaches have led to a map of the architecture and energy transfer pathways between LHC pigments. Still, controversies remain regarding the role of specific carotenoids in light-harvesting and photoprotection, obligating the need for high-resolution techniques capable of identifying excited-state signatures and molecular identities of the various pigments in photosynthetic systems. Here we demonstrate the successful application of femtosecond stimulated Raman spectroscopy (FSRS) to a multichromophoric biological complex, trimers of LHCII. We demonstrate the application of global and target analysis (GTA) to FSRS data and utilize it to quantify excitation migration in LHCII trimers. This powerful combination of techniques allows us to obtain valuable insights into structural, electronic, and dynamic information from the carotenoids of LHCII trimers. We report spectral and dynamical information on ground- and excited-state vibrational modes of the different pigments, resolving the vibrational relaxation of the carotenoids and the pathways of energy transfer to chlorophylls. The lifetimes and spectral characteristics obtained for the S1 state confirm that lutein 2 has a distorted conformation in LHCII and that the lutein 2 S1 state does not transfer to chlorophylls, while lutein 1 is the only carotenoid whose S1 state plays a significant energy-harvesting role. No appreciable energy transfer takes place from lutein 1 to lutein 2, contradicting recent proposals regarding the functions of the various carotenoids (Son et al. Chem.2019, 5 (3), 575–584). Also, our results demonstrate that FSRS can be used in combination with GTA to simultaneously study the electronic and vibrational landscapes in LHCs and pave the way for in-depth studies of photoprotective conformations in photosynthetic systems.